A case of schwannoma at the origin of the right recurrent laryngeal nerve resected under uniportal video‐assisted thoracic surgery. Issue 9 (23rd August 2022) - Kamimura, Go; Ueda, Kazuhiro; Takeda, Aya; Maeda, Koki; Aoki, Masaya; Sato, Masami
Abstract: Mediastinal neurogenic tumours are mostly derived from sympathetic nerves and intercostal nerves, and vagus nerve‐derived schwannomas are rare. We encountered a tumour originating from the origin of the recurrent laryngeal nerve that was accompanied by the azygos lobe, which made it difficult to approach; it was ultimately able to be removed via uniportal video‐assisted thoracic surgery. This case involved a 63‐year‐old female patient. There were no particular symptoms, but an abnormal chest shadow was noted on an imaging examination. Chest imaging revealed a smooth‐surfaced mass in the upper right mediastinum with the azygos lobe. A diagnosis of schwannoma was made by imaging, and the patient underwent resection via uniportal video‐assisted thoracic surgery. The tumour, which originated from the origin of the right recurrent laryngeal nerve, was sharply removed without causing recurrent laryngeal nerve palsy. Abstract : Mediastinal neurogenic tumors are often derived from sympathetic nerves and intercostal nerves, and schwannomas originating from the intrathoracic vagus nerve are rare. In the present case, we performed uniportal video‐assisted thoracic surgery for schwannoma of the origin of the recurrent laryngeal nerve. This case was complicated with the azygos lobe, but recurrent laryngeal nerve palsy was avoided even after surgery, so we report it with some consideration.